2019
DOI: 10.4103/jfmpc.jfmpc_276_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diabetic patients' adherence to insulin injections on basal-bolus regimen in diabetic care center in Saudi Arabia 2018: Cross sectional survey

Abstract: Background: Since insulin became a focal point of diabetes management, several studies have been carried out to monitor and improve patient outcomes. Adherence insulin therapy is an important part of diabetes management. Aim: This study reviews the responses of patients being managed in a diabetic care setting in monitoring their adherence to basal bolus insulin therapy. Method: A pre-validated questionnaire containing 18 questions was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Since the burden of diabetes mellitus is linked with its control, which is directly related to adherence, nonadherence should be considered a significant health concern of priority [13]. Our study indicated that 40.7% of diabetic patients forget to take insulin doses every week.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Since the burden of diabetes mellitus is linked with its control, which is directly related to adherence, nonadherence should be considered a significant health concern of priority [13]. Our study indicated that 40.7% of diabetic patients forget to take insulin doses every week.…”
Section: Discussionmentioning
confidence: 73%
“…Section V had items related to the factors that may increase the adherence of insulin injections, and the participants were asked to select the factors according to their understanding. A similar type of questionnaire has been used in the literature [13]. The questionnaire was translated from English to Arabic through a forward-and-backward translation process.…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous IDMPS waves, we have reported the independent and positive association of high levels of education and access to diabetes education with SMBG, self-titration of insulin and glycaemic control in both patients with T1D or T2D [ 17 ]. In Saudi Arabia and Cameroon, patient literacy was closely associated with adherence to therapies [ 33 , 34 ]. Low education level and poverty have been associated with increased incidence of all-cause and cardiovascular mortality in patients with diabetes after adjusting for confounders [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with reduced insulin adherence include smoking, young age, low socioeconomic status, level of scholarship, presence of other comorbidities, and polypharmacy [ 19 ]. In our study, only the frequency of administration exhibited a significant difference in practices toward insulin injection (p = 0.049); patients who administered insulin injection three times daily had the best practices toward insulin injection when compared to other patients.…”
Section: Discussionmentioning
confidence: 99%